The Phonetics of Aspiration in English and Arabic (The International Journal for Scientific Research, 2025)
This research focuses on aspiration’s phonetic phenomenon in English as well as Arabic, testing every acoustic feature, phonological importance and occurrence in English and Arabic. It is realized as a breath burst coming after the specific consonants’ releasing. In English, it can be truly important, specifically in a voiceless plosive like /t/, /k/ and /p/. On the other hand, there is a lack of such consonants in Arabic, which instead depends on other phonological and articulatory techniques for distinguishing any sound. Throughout a comparative phonetic analyzing, the study examines the way of producing and perceiving aspiration by Arabic as well as English speakers. The research uses articulatory descriptions as well as spectrographic analyzing for highlighting every cross-linguistic similarity and difference. Furthermore, these outcomes’ implications are under discussion concerning the acquisition of a second language, especially the difficulties which every Arabic speaker might suffer from as he/she studies English pronunciation. The research gives a bigger comprehending of aspiration phonetically and phonologically, and how it is related to the contexts that are cross -linguistic.
Keywords: Aspiration; Articulation; Pedagogy; Acoustics; Glottalization; Assimilation; Plosives